2010
DOI: 10.1080/20786204.2010.10874006
|View full text |Cite
|
Sign up to set email alerts
|

Emotional reactions of medical doctors and students following the loss of their patients at the Dr George Mukhari Hospital emergency unit, South Africa

Abstract: SA Fam Pract 2010;52(4):356-363Background: Studies on death and dying predominantly emphasise the needs of the dying patient and the process of bereavement. Few studies have focused on the reactions of medical doctors and students when the patients they have cared for die. Methods:The aim of the study was to explore the thoughts and feelings of doctors and medical students who have lost patients while under their care at the Dr George Mukhari Hospital emergency unit in Ga-Rankuwa, South Africa. The participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 18 publications
(13 reference statements)
0
33
0
1
Order By: Relevance
“…Most existing research from low-resource settings on healthcare providers' responses to death has focused on emotional distress and burnout [6,7]. Our work showed elements of depersonalization, as is documented throughout the world [16], but was dominated by providers' commitment to pushing on and providing the best care possible.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Most existing research from low-resource settings on healthcare providers' responses to death has focused on emotional distress and burnout [6,7]. Our work showed elements of depersonalization, as is documented throughout the world [16], but was dominated by providers' commitment to pushing on and providing the best care possible.…”
Section: Discussionmentioning
confidence: 92%
“…Studies from lowresource settings have documented emergency healthcare providers' emotional distress surrounding death, including feelings of blame and having to reject their emotions. These providers noted particular struggles with pediatric deaths, which felt unnatural and exceptionally tragic, as well as in situations where they were unable to grieve previous losses [6]. A South African study documented high levels of burnout among hospice workers, attributed both to the nature of working with dying patients as well as various other work-related stressors [7].…”
Section: Introductionmentioning
confidence: 98%
“…Contrary to the traditional practice of mindfulness, which focuses on one's awareness of the present moment, reflective silence allows individuals to consider retrospective events and the feelings that were experienced. Ofri explains that this may help facilitate health care professionals’ exploration of the deeper context of what it means to be ‘in medicine’, which is likely to benefit both the health care professional and the patient …”
Section: Recommended Strategies and Educational Exercisesmentioning
confidence: 99%
“…In these settings, the mistakes were often forgotten and not considered for future safety reasons, even when they were communicated to the group or to the person immediately higher in hierarchy. Masia, Basson, and Ogunbanjo () interviewed doctors who had suffered the loss of a patient during the 48 hr before the interview and one of the reoccurring themes was blame. Fast and Tiedens () showed that blaming is socially contagious, in the sense that exposure to blaming attributions regarding one event (failure) leads to blaming attributions regarding another unrelated event.…”
Section: Discussionmentioning
confidence: 99%